Engaging Primary Care Professionals and People at Risk of Type 2 Diabetes in the Design of PREDIABETEXT, a Multifaceted Digital Intervention Aimed at Preventing Type 2 Diabetes: A Qualitative Study - Maria Jesús Serrano-Ripoll; Rocío Zamanillo-Campos; Sofía Mira Martínez; Maria Antònia Fiol-deRoque; Narges Malih; Escarlata Angullo-Martínez; Ignacio Ricci-Cabello (Diabetology)
Objectives: This study aims to explore perspectives and opinions from healthcare professionals and people at risk of type 2 diabetes mellitus (T2DM) to inform the design of PREDIABETEXT, a new digital multifaceted intervention to prevent T2DM. Methods: in this qualitative study, we purposefully recruited 15 healthcare professionals (doctors and nurses) working in primary healthcare centers in Mallorca (Spain), and 15 of their patients at risk of T2DM (HbA1c 6–6.4%, and/or fasting plasma glucose 110–125 mg/dL). We collected the data through semi-structured phone interviews, using an interview guide aimed at gathering participants’ views about the two PREDIABETEXT proposed co-interventions (educational intervention targeted at professionals and delivered as an online training course, and behavioral intervention targeted at individuals at risk of T2DM and delivered using SMS short text messages). The interviews were audio-recorded, verbatim transcribed, and analyzed using a thematic analysis approach. Results: Primary healthcare professionals valued a prediabetes training course for standardizing care and supporting diabetes prevention. They preferred a blended format with content on early detection, intervention, and monitoring. They perceived SMS reminders to their patients as potentially useful for reinforcing guidelines and improving care. Individuals at risk of T2DM, who faced challenges maintaining a healthy diet and exercise routine, viewed SMS as potentially motivational and informative, offering suggestions on content, format, and frequency to enhance its intended benefits. Conclusions: This qualitative study provided valuable insights from primary care professionals and people at risk of T2DM that will inform the user-centered design of the PREDIABETEXT intervention.